Optimization Study in Dunaliella salina EU5891200 Isolated in Salt pans of Tamil Nadu, South India - R. Rajkumar, L. Sheeja, S. Divya and R. Rengasamy, K.R. Jayappriyan* (Recent Research in Science and Technology, 2010)
This study examined the effect of different pH, light intensity and different concentrations of NaNO3, NaH2PO4 and NaCl on the kinetics of growth, total carotenoids accumulated in Dunaliella salina EU5891200, a micro algal strain isolated from the salt pans of Tamil Nadu, South India. Results indicated that the highest amount of carotenoids detected grown at pH 8, 40 ÂµEm-2s-1 light intensity had maximum production of total carotenoids. Lower salinity of 1.0 M NaCl favored high accumulation of total carotenoids. The amounts of total carotenoids recorded at 1.0 mM NaNO3 for D. salina had 20% more than the control. Phosphate was found to greatly influence the accumulation of total carotenoids (120.0Âµg/mL) in the isolate.